In vitro pharmacological evaluation of multitarget agents for thromboxane prostanoid receptor antagonism and COX-2 inhibition. (January 2016) - Hoxha, Malvina; Buccellati, Carola; Capra, Valérie; Garella, Davide; Cena, Clara; Rolando, Barbara; Fruttero, Roberta; Carnevali, Silvia; Sala, Angelo; Rovati, G.Enrico; Bertinaria, Massimo
Graphical abstract: Abstract: Purpose: Patients with high cardiovascular risk due to ageing and/or comorbidity (diabetes, atherosclerosis) that require effective management of chronic pain may take advantage from new non-steroidal anti-inflammatory drugs (NSAIDs) that at clinical dosages may integrate the anti-inflammatory activity and reduced gastrointestinal side effects of selective cyclooxygenase-2 (COX-2) inhibitor (coxib) with a cardioprotective component involving antagonism of thromboxane A2 prostanoid (TP) receptor. Methods: New compounds were obtained modulating the structure of the most potent coxib, lumiracoxib, to obtain novel multitarget NSAIDs endowed with balanced coxib and TP receptor antagonist properties. Antagonist activity at TP receptor (pA2 ) was evaluated for all compounds in human platelets and in an heterologous expression system by measuring prevention of aggregation and Gq-dependent production of intracellular inositol phosphate induced by the stable thromboxane A2 (TXA2 ) agonist U46619. COX-1 and COX-2 inhibitory activities were assessed in human washed platelets and lympho-monocytes suspension, respectively. COX selectivity was determined from dose–response curves by calculating a ratio (COX-2/COX-1) of IC50 values. Results: The tetrazole derivative18 and the trifluoromethan sulfonamido-isoster20 were the more active antagonists at TP receptor, preventing human platelet aggregation and intracellular signalling, with pA2 values statistically higher from that of lumiracoxib. Comparative data regarding COX-2/COX-1 selectivity showed that while compounds18 and7 were rather potent and selective COX-2 inhibitor, compound20 was somehow less potent and selective for COX-2. Conclusion: These results indicate that compounds18 and20 are two novel combined TP receptor antagonists and COX-2 inhibitors characterized by a fairly balanced COX-2 inhibitor activity and TP receptor antagonism and that they may represent a first optimization of the original structure to improve their multitarget activity.